Secrecy and absence in the residue of covert drone strikes. (March 2017) - Kearns, Oliver
Abstract: By focusing on the materials and practices that prosecute drone warfare, critical scholarship has emphasised the internal state rationalisation of this violence, while positioning secrecy and absence as barriers to research. This neglects the public existence of covert U.S. drone strikes through the rumours and debris they leave behind, and the consequences for legitimisation. This article argues that by signifying the possible use of covertness, the public residue of unseen strikes materialises spaces of suspected secrecy. This secrecy frames seemingly arbitrary traces of violence as significant in having not been secreted by the state, and similarly highlights the absence in these spaces of clear markers of particular people and objects, including casualties. Drawing on colonial historiography, the article conceptualises this dynamic as producing implicit significations or intimations, unverifiable ideas from absences, which can undermine rationalisations of drone violence. The article examines the political consequences of these allusions through an historical affiliation with lynching practice. In both cases, traces of unseen violence represent the practice as distanced and confounding, prompting a focus on the struggle to comprehend. Intimations from spaces of residue position strikes as too ephemeral and materially insubstantial to understand. Unlike the operating procedures of drone warfare, then, these traces do not dehumanise targets. Rather, they narrow witnesses' ethical orientation towards these events and casualties, by prompting concern with intangibility rather than the infliction of violence itself. A political response to covert strikes must go beyond 'filling in' absences and address how absence gains meaning in implicit, inconspicuous ways. Highlights: Critical scholarship on drone warfare has neglected the political dynamics of secrecy and absence. Rumours and debris of covert drone strikes shape public spaces of suspected secrecy. Absences in these spaces produce intimations of unverifiable ideas, undermining the rationalisation of strikes. Representation of unseen strikes through their public traces echoes historical coverage of lynching. Strikes materialise as too ephemeral and insubstantial to comprehend, marginalising ethical concern towards casualties.